Chronic Pain: A Red Herring or Risk Factor in the Management of Patients Receiving Opioid Substitution Therapy - Dennis, Brittany Burns (My University, 2015)
Background: The consequences of continued opioid abuse among patients treated with opioid substitution therapy (OST) are serious and can result in abnormal cardiovascular function, overdose, and mortality. Conflicting evidence exists that both implicates and refutes the role of chronic non-cancer pain (CNCP) as a major risk factor for continued opioid abuse within the addiction treatment setting. This thesis aims to 1) evaluate the impact of chronic pain on the treatment outcomes of patients with opioid addiction receiving OST, 2) determine whether a clinical or inflammatory profile exists to distinguish pain in this population, 3) explore the sources of heterogeneity in previous studies examining this question, 4) determine the best therapy for patients with chronic pain, and 5) evaluate the most effective treatment for opioid addiction. We anticipate chronic pain to be an important predictor of continued opioid abuse such that patients with comorbid pain will require careful consideration when managed on OST. Methods: We systematically reviewed the literature to determine the impact of pain in opioid addiction patients receiving methadone maintenance treatment (MMT). We determined the clinical and inflammatory profile of MMT patients using data from the Genetics of Opioid Addiction (GENOA) research collaborative between the Canadian Addiction Treatment Centres (CATC) and the Population Genomic Program. GENOA is a prospective cohort study aimed to determine the genetic, biological, and psychosocial determinants of treatment prognosis for opioid addiction patients receiving MMT. GENOA recruits patients ≥ 18 years of age meeting the DSM-IV criteria for opioid dependence. All GENOA participants are receiving MMT for the management of opioid addiction. Baseline data from the GENOA pilot study (n=235) were used to evaluate the impact of pain on illict opioid use behaviour and determine the clinical and inflammatory profile of patients with comorbid pain. We explored sources of heterogeneity in previous studies using data from the full-phase GENOA study (n=444), examining the prognostic value of different pain measures for predicting illicit opioid use. We then performed a multiple treatment comparison of all opioid substitution and antagonist therapies in efforts to determine the best intervention for improving treatment outcomes for patients with comorbid pain. We lastly determined the most effective treatment for opioid addiction by performing a network meta-analysis using data from a systematic review of opioid maintenance therapy trials. Results: Our initial systematic review confirmed a lack of consensus in the literature, whereby some studies suggest pain increases risk for illicit opioid use and other studies suggest pain has no effect on substance use behaviour. Findings from the analysis of GENOA pilot data confirmed chronic pain to be an important predictor of sustained opioid abuse and also showed patients with pain to have elevated Interferon-Gamma. Using data from the GENOA prospective cohort study we determined the Brief Pain Inventory (a commonly used pain measurement in pervious studies) to be highly sensitive with poor prognostic value. Our final reviews propose 1) there is limited evidence to suggest any OST is superior for managing patients with comorbid pain, and 2) heroin and high-dose methadone are the most effective treatments for improving treatment retention. The final systematic review and network meta-analysis in this thesis also highlights a major problem in the treatment of opioid use disorders, primarily the lack of consensus as to what outcomes matter for determining success in patients with addiction. Conclusion: Patients with comorbid pain and addiction are at high-risk for continued opioid abuse and should be managed closely by clinicians administering OST. Contention in the previous literature likely resulted from the use of pain measurements with poor prognostic value. No OST demonstrated superiority for managing patients with chronic pain. While our findings indicate heroin is the most effective treatment across multiple endpoints, we use this thesis to provide readers with 1) a sense of the feasibility issues associated with heroin administration, 2) a summary of the limitations of this evidence base, and 3) recommendations for how to improve the addiction trials’ design for future research.
Keywords: chronic pain; methadone; opioid substitution therapy; opioid agonist treatment; methadone maintenance treatment; opioid addiction; addiction; opioid induced hyperalgesia